Pelaksanaan Pembagian Harta Warisan Menurut Hukum Adat di Kecamatan Gondangrejo, Kabupaten Karanganyar: Sebuah Studi Kasus - Haq, Fatah Imanuddin; Lestari, Ahdiana Yuni (Jurnal Analisis Hukum, 2025)
This study explores inheritance distribution based on customary law in Gondangrejo District, Karanganyar Regency. Although the majority of the population is Muslim, inheritance practices are predominantly shaped by Javanese traditions and abangan Islamic culture rather than Islamic law. Using a qualitative method, the research identifies three common patterns: segendong sepikul (male heirs receive double), dum-dum ketupat (equal distribution), and consensus-based division. Assets are viewed as joint marital property, without distinction between individual and shared ownership. Uniquely, parts of the inheritance may be transferred before the testator’s death through oral messages or symbolic gifts. Local customs, especially selametan rituals, influence the timing of distribution, which is commonly expected within six months after death. The findings highlight that harmony, mutual agreement, and cultural values play a more dominant role than formal legal rules. In Gondangrejo, inheritance practices reflect a deep connection to local wisdom and tradition, emphasizing social cohesion over rigid legal structure.